Is there any link between commodity price and monetary policy? Evidence from Australia - Hassan, A.; Salim, Ruhul (The Economic society of Australia, 2011)
The aim of this paper is to examine whether the commodity prices predict inflation, unemployment and short term interest rate in Australia. Advanced time series econometric modeling such as vector autoregressive model, cointegration and granger causality are used for this purpose. The empirical results show that three commodity prices (COMRL, COMNRL and COMBSMTL) precede inflation. However, no evidence of reverse causation is found. These findings have important implication for monetary authority. Inflation targeting experience has so far been hit by positive supply shocks. In case of negative supply shock, commodity price may be useful in singling out the likely direction of inflation.